Psychosocial morbidity profile in a community based sample of low back pain patients - Mir Mahmood Asrar (Nature Portfolio, 2021)
Abstract Low back pain (LBP) is a major health concern and is closely associated with psychosocial morbidity and diminished Health-related quality of life (HRQoL). This is minimally investigated in community-based samples of developing nations like India. This study is aimed to specifically investigate the exposure-outcome associations between LBP and burden of disability (Modified Oswestry questionnaire (MODQ)), psychological morbidities (Depression, Anxiety and Stress Scale (DASS-21)), and HRQoL (Short Form -12 version 2 (SF12V2). A Cross-sectional study using a community-based sample of LBP positive population was conducted. The range of treatment options sought was also collected. Chi-square tests and independent t-test were used to analyze the data. Of 1531 recruited participants, 871(57%) were identified as LBP positive of whom 60% were females. Mean (SD) of age and pain intensity of LBP patients was 33 (11) years and numeric rating scale4.2 (2.6) respectively. Two-third reported minimal/moderate disability. Mean (SD) scores of depression 11.87 (4.05), anxiety (8.32), stress 13.7 (5.98), physical and mental summary scores of SF-12v2 were 47.9 (7.4) and 42.2 (10.4). A multitude of remedial options was sought for the ailment. LBP causes significant disability and psychological morbidity among affected population. This may adversely affect their HRQoL and subsequently productivity. Acupuncture was a preferred treatment sought by Indian LBP patients.